(untitled) (KULT_online, 2015)
Using the example of advertising, Hannes Krämer’s monograph offers a detailed empirical study of contemporary ’creative’ work practices. His ethnographic methods are a relevant addition to existing macro-perspectives on creativity. Stressing the multiple stages and materializations in the daily production of creativity, creative work appears to be a social figuration that can be distinguished from other forms of wage labour with respect to subject, product, and practices of work.